2018
DOI: 10.1126/science.aat6768
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic classification of clinical phenotypes in neuroblastoma

Abstract: Neuroblastoma is a pediatric tumor of the sympathetic nervous system. Its clinical course ranges from spontaneous tumor regression to fatal progression. To investigate the molecular features of the divergent tumor subtypes, we performed genome sequencing on 416 pretreatment neuroblastomas and assessed telomere maintenance mechanisms in 208 of these tumors. We found that patients whose tumors lacked telomere maintenance mechanisms had an excellent prognosis, whereas the prognosis of patients whose tumors harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
342
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(369 citation statements)
references
References 48 publications
17
342
3
7
Order By: Relevance
“…However, in the ongoing European LINES trial, the effect of the CNA in this group is being prospectively studied. Recent research concluded that the combination of telomere maintenance activity and aberrations in the RAS and TP53 pathways can predict unfavorable outcome in low‐risk patients . It would be interesting to see if these parameters are helpful in making treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the ongoing European LINES trial, the effect of the CNA in this group is being prospectively studied. Recent research concluded that the combination of telomere maintenance activity and aberrations in the RAS and TP53 pathways can predict unfavorable outcome in low‐risk patients . It would be interesting to see if these parameters are helpful in making treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between the presence of variations in CRG/EMG and other genetic factors associated with poor outcome in NB should be determined in future studies and larger series, such as the overall mutational burden 50 or factors contributing to a mechanistical classification of NB including mutations of the RAS: MAPK pathway and telomere maintenance mechanisms. 51 New treatment strategies are necessary for patients with high-risk NB, and our data further highlight the potential interest of drugs modulating chromatin remodeling processes. Histone deacetylase inhibitors (HDACi) or DNA methyltransferase inhibitors were the first epigenetic compounds to reach clinical trials with potential benefits in some patients with CRG/EMG variations.…”
Section: Discussionmentioning
confidence: 57%
“…This suggests that cases harboring CRG/EMG variations might present more aggressive disease or that salvage treatment used at relapse might potentially be more efficient in cases showing no CRG/EMG variation. Correlations between the presence of variations in CRG/EMG and other genetic factors associated with poor outcome in NB should be determined in future studies and larger series, such as the overall mutational burden or factors contributing to a mechanistical classification of NB including mutations of the RAS:MAPK pathway and telomere maintenance mechanisms …”
Section: Discussionmentioning
confidence: 99%
“…The five described variables appear to cover the impact of MYCN oncogene ( MYCN ) amplification, increased lactate dehydrogenase levels, and other risk factors mentioned. In the future, novel omics technologies may provide better insights into the molecular mechanism and potentially better explain clinical courses right from the first diagnosis . Tumor material for molecular investigations was not available in most cases of this series.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, novel omics technologies may provide better insights into the molecular mechanism and potentially better explain clinical courses right from the first diagnosis. 13,14 Tumor material for molecular investigations was not available in most cases of this series. The match of phenotype and genotype is an important task for the future.…”
Section: Discussionmentioning
confidence: 99%